2020
DOI: 10.3390/ijms21249412
|View full text |Cite
|
Sign up to set email alerts
|

IL-24 Negatively Regulates Keratinocyte Differentiation Induced by Tapinarof, an Aryl Hydrocarbon Receptor Modulator: Implication in the Treatment of Atopic Dermatitis

Abstract: Skin barrier dysfunction, including reduced filaggrin (FLG) and loricrin (LOR) expression, plays a critical role in atopic dermatitis (AD) development. Since aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, mediates keratinocyte differentiation, it is a potential target for AD treatment. Recently, clinical studies have shown that tapinarof, an AHR modulator, attenuated the development of AD. To examine the molecular mechanism involved in this, we analyzed tapinarof-treated normal human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
3
23
1
Order By: Relevance
“…Based on TFEA indicating enrichment for motifs for each of these factors among active enhancers at 120 min versus vehicle (false discovery rate <0.05), our data implicate the MEF2 family in mediating secondary gene expression responses to WSP. In addition to this family, the bZip transcription factor, MAFF , LHX4 , a lim homeobox factor, and the cytokine, IL-24 , which is implicated in lung and airway remodeling in response to different inflammatory stimuli, were also among the set of AHR targets we identified ( 52 , 53 , 54 , 55 ). Thus, the short-lived primary transcriptional response to WSP mediated by AHR includes targets that likely contribute to more sustained changes in gene expression, possibly in collaboration with other rapid transcriptional effectors of the response to WSP, such as the TCF–SRF family.…”
Section: Discussionmentioning
confidence: 97%
“…Based on TFEA indicating enrichment for motifs for each of these factors among active enhancers at 120 min versus vehicle (false discovery rate <0.05), our data implicate the MEF2 family in mediating secondary gene expression responses to WSP. In addition to this family, the bZip transcription factor, MAFF , LHX4 , a lim homeobox factor, and the cytokine, IL-24 , which is implicated in lung and airway remodeling in response to different inflammatory stimuli, were also among the set of AHR targets we identified ( 52 , 53 , 54 , 55 ). Thus, the short-lived primary transcriptional response to WSP mediated by AHR includes targets that likely contribute to more sustained changes in gene expression, possibly in collaboration with other rapid transcriptional effectors of the response to WSP, such as the TCF–SRF family.…”
Section: Discussionmentioning
confidence: 97%
“…Tapinarof also inhibited T cell expansion and Th17-cell differentiation in vitro, reducing IL-17A and IL-17F secretion, which is relevant for PS treatment [242]. Furthermore, tapinarof treatment restores the downregulation of FLG and LOR expression induced by IL-4, a key cytokine in AD [243]. Finally, tapinarof induces AHR-mediated secretion of IL-24, which downregulates FLG and LOR expression and alters keratinocyte differentiation [243,248,249].…”
Section: Tapinarof-a Novel Treatment For Ps and Admentioning
confidence: 90%
“…High throughput profiling studies revealed that tapinarof binds directly to AHR resulting in downregulation of inflammatory cytokines, including IL-17A, IL-17F, IL-19, IL-22, IL-23, and IL-1β in the IMQ-induced PS model [242]. Tapinarof also induces the expression of skin barrier genes related to keratinocyte differentiation in an AHR-dependent manner, including FLG and LOR [242,243] (Table 1). In fact, tapinarof displayed a pattern of biological responses reminiscent of that of the AHR agonist FICZ in the IMQ model [105].…”
Section: Tapinarof-a Novel Treatment For Ps and Admentioning
confidence: 99%
“… Liu et al (2015) identified the AhR-dependent transcriptional upregulation of the IL24 gene in normal human chorionic villi. TCDD, FICZ, and tapinarof also can activate the expression of IL24 through AhR in various cell types ( Vu et al, 2020 ). Besides IL24 and CYP1B1, we also found other migration-related genes that may be regulated by AhR through transcriptome sequencing and DRE analysis.…”
Section: Discussionmentioning
confidence: 99%